Znamy się tylko z widzenia? Polacy o kontaktach z Niemcami w świetle badań Lubuskiego Sondażu Społecznego = We know each other only by sight? The Poles about their contacts with the Germans in the light of the Lubus Social Survey - Trzop, Beata; Zielińska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is to present the characteristic of behavior of the inhabitants of the Polish-German borderland associated with the proximity of the border with Germany. The empirical base for this study are data from longitudinal studies conducted in the Institute of Sociology (University of Zielona Gora) called Lubus Social Survey. The analyzed issues are located in the area of interest of sociology of borderlands and the diffusion of culture.
Keywords: socjologia pogranicza; kontakty polsko-niemieckie; dyfuzja kultury; sąsiedztwo; badania sondażowe; sociology of borderland; polish-german relationships; cultural diffusion; neighborhood; social survey